Wavelet analysis and consensus algorithm-based fault-tolerant control for smart grids - Han, Yunlong (Frontiers in Energy Research, 2023)
In this paper, the voltage and frequency regulation problems are investigated for smart grids under the influence of faults. To solve those problem, a wavelet analysis and consensus algorithm-based fault-tolerant control scheme is proposed. Specifically, the wavelet analysis technique is introduced to determine whether there exist faults or not in the smart grids. Then, a distributed fault estimator is designed to estimate the attack signals. Based on this estimator state, a distributed fault-tolerant controller is designed to compensate for the faults. It is theoretically shown that the developed method can achieve the voltage regulation and frequency objectives. Finally, a smart grid with four distributed generations is constructed in MATLAB/Simulink for simulation to validate the effectiveness.